Effect of CaO-Al2O3-SiO2 molar ratio on compressive strength, reaction products, and strength prediction model of CaO-activated materials - Gaoyu Liao; Takafumi Noguchi (Case Studies in Construction Materials)
Low-carbon cementitious materials play a pivotal role in combating climate change by offering sustainable alternatives to ordinary Portland cement (OPC), thereby significantly reducing carbon emissions in the construction industry. CaO-activated materials (CAM), as one of the low-carbon cementitious materials, exhibit promising potential for replacing OPC, given their relatively lower carbon emissions and cost-effectiveness. However, due to the diverse origins and significant disparities in the chemical and mineral compositions of the raw materials used in CAM, achieving consistent performance akin to OPC proves challenging. This study seeks to elucidate the inherent correlation between the chemical composition and mechanical properties of CAM. It presents a comprehensive investigation into the impact of the CaO-Al2O3-SiO2 molar ratio on the compressive strength and reaction products of CAM. Raw materials, including slag, metakaolin, and shirasu (volcanic ash), were employed to adjust the CaO-Al2O3-SiO2 molar ratio of the precursor, with CaO serving as the activator for various ratios. The study proposes the ''CAM strength index'' to effectively rank CAM strength and identifies a logarithmic relationship between CAM strength and the C/(S+A) molar ratio. Furthermore, the proposed “CAM model” accurately predicts CAM strength evolution by measuring reactive CaO-Al2O3-SiO2 content, offering a robust tool for this purpose.